Tinjauan Maqashid Syariah Atas Perkawinan Beda Agama : (Analisis Komprehensif SEMA No. 2 Tahun 2023) - Ibnu Hamzah, Saiful (Muhammadiyah University of Surabaya, 2025)
This article provides a comprehensive analysis of Supreme Court Circular Letter (SEMA) No. 2 of 2023 concerning the registration of interfaith marriages in Indonesia, specifically through the lens of Maqasid Syariah. It delves into the legal, philosophical, religious, and human rights dimensions, presenting both arguments supporting and opposing the SEMA. The research employs a normative juridical method, utilizing statutory, conceptual, and case approaches, drawing from primary and secondary legal materials, including relevant jurisprudence. The analysis reveals that SEMA No. 2 of 2023, while aiming for legal certainty and uniformity in interpreting the Marriage Law, faces significant challenges. Its proponents emphasize legal positivism, natural law, and Pancasila values to uphold the sacredness of marriage and public morality, often aligning with the preservation of religion and lineage as per Maqasid Syariah. Conversely, opponents argue that the SEMA infringes upon human rights, contradicts legal pluralism, and possesses weak legal standing as a circular letter. The study highlights inconsistencies in judicial interpretations, particularly regarding Constitutional Court Decision No. 71/PUU-XX/2022 and post-SEMA district court rulings, which complicate its practical implementation. The SEMA's restrictive stance may inadvertently lead to legal subterfuge and create legal uncertainties for families, especially concerning children's status and inheritance rights, which can be viewed as detrimental to the preservation of offspring and property in Maqasid Syariah. This article concludes by suggesting the need for legislative reform to harmonize marriage laws with Indonesia's pluralistic society and human rights principles, while also considering the broader objectives of Maqasid Syariah. Keywords: Interfaith Marriage, SEMA No. 2 Tahun 2023, Maqasid Syariah.